You know them about the children and the interactions in the net - Manuel Jacinto Sarmento; Sandra Marlene Barra (Universidade Federal de Santa Catarina, 2008)
Most of the studies that you/they lean over about the technologies of information and communication (TIC) and the children try to demonstrate the potentialities and benefits of the first ones in relation to Mondays. The inverse perspective-the one that the children do of the technologies - it is much less documented in the research. Starting from the theoretical picture of reference of the Sociology of the Childhood, it tries to clear the devices, the manners and the elaboration processes and to re-do of the you know about the children in the ambit of the interactions of pairs in the net.